Perylene based novel mixed matrix membranes with enhanced selective pure and mixed gases (CO2, CH4, and N2) separation - Saqib, S. (Elsevier B.V., 2020)
A combination of organic filler exhibiting CO2 philic nature with a polymer to develop mixed matrix membranes (MMMs) can capture CO2 efficiently. This work reports the synthesis of perylene filler and polysulfone (PSf)-based MMMs via solution casting method. The successful incorporation of fillers, uniformity/asymmetric, and amorphous nature of MMMs were investigated by FT-IR, FESEM, and PXRD analysis, respectively. MMMs demonstrated high thermal stability with significant weight retention over 750 Â°C investigated by TGA analysis. The existence of Lewis's basic functionalities, hydrogen bonding, and Ï-Ï bonds between the filler-polymer resulted in the formation of highly CO2 philic structure. Results revealed that the perylene is found to be highly porous (1050 m2/g) and compatible with the PSf to form additional channels, enhancement of free PSf volume and tendency to prevent the agglomeration and non-selective interfacial voids. It demonstrated improved permeabilities of CO2 (138), CH4 (59), and N2 (60) without any significant variation in selectivities CO2/CH4 (3) and CO2/CH4 (7). Similarly, mixed gas permeabilities were improved for (CO2âCH4 â 119) and (CO2âN2 â 116) along with enhanced selectivities (CO2âCH4 â 50) and (CO2âN2 â 46). Furthermore, the influence of temperature on gas permeabilities revealed improved kinetic energy and flexibility in the polymer chains. The mechanical strength analysis revealed high filler-polymer compatibility. These results revealed great potential of MMMs for efficient CO2 separation from pre- and post-combustion sources. Â© 2019 Elsevier B.V.